Toward Measuring Chinese EFL Teachers’ Resilience: The Role of Teachers’ Enjoyment, Anger, and Anxiety - Gan, Lu; Gao, Yonggang; Wu, Jinwen (Frontiers in Psychology, 2022)
Teachers have been regarded for many years as one of the most impactful elements with a significant function in educational and learning contexts. Several studies have been conducted on teachers and their performances in the classes. Positive psychology has focused on both the constructive and deconstructive feelings that teachers encounter in the process of teaching. Among the investigated elements, enjoyment anger, and anxiety can be regarded more significant in the relevant literature. The current research, thus, clarifies their association and connection with Chinese language educators’ resilience. To this end, 464 male and female Chinese EFL teachers participated in the present study, and their enjoyment, anger, anxiety, and resilience were inspected by completing the associated questionnaires. The data analysis indicated that there is a substantial correlation between teachers’ resilience and their emotions. Similarly, it is concluded that the best predictor of teachers’ resilience is enjoyment. Also, some academic suggestions for the study regarding the development of teachers’ resilience in educational situations are proposed.